Effect Of Forensic Accounting Services On Fraud Reduction In The Nigerian Banking Industry - Henry, Agbaje. W.; Ganiyu, Adeniran Busari (Advances in Social Sciences Research Journal, 2017)
The study dwelt on the effects of forensic accounting services on fraud reduction in the Nigerian banking industry. The specific objectives focused on effect of forensic accounting services on treasury and forex operation and effect of forensic accounting services on loan processing and cash management. To achieve these objectives, survey research method was adopted for the study while primary data were collected, questionnaire were administered. The correlation regression model was used to analyze the data. The study sought to find out to what level the forensic accounting services are able to fulfil this mandate and investigate problems that occur when forensic accounting services is not adopted in the operations of Nigerian banking industry. It established the role of forensic accounting accountant in banking operations. The internationally recognized procedures in detecting and investigating these fraud were discussed. The findings of the study revealed that forensic accounting services reduce fraud in banking industry. The implication of this is that pragmatic policy options needed to be taken on internal control system and effective management of core banking operations like cash management, treasury operation loan processing and FOREX transaction must be diligently guided and subjected to forensic accounting. It was also recommended that maximization of customer’s interest should be major focus without contravention of regulations set out by Central Bank of Nigeria.